Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.foodres.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Insights into milk-clotting activity of latex peptidases from Calotropis procera and Cryptostegia grandiflora

Abstract: Latex fractions from Calotropis procera, Cryptostegia grandiflora, Plumeria rubra, and Himatanthus drasticus were assayed in order to prospect for new plant peptidases with milk-clotting activities, for use as rennet alternatives. Only C. procera and C. grandiflora latex fractions exhibited proteolytic and milk-clotting activities, which were not affected by high concentrations of NaCl and CaCl. However, pre-incubation of both samples at 75°C for 10min eliminated completely their activities. Both proteolytic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 51 publications
4
11
0
Order By: Relevance
“…Interestingly, C. procera and C. grandiflora latex peptidases did not undergo autolysis and were active even after a 24 h incubation at 37 ºC (Freitas et al, 2016). All these biochemical characteristics strengthen the evidence that peptidases from C. procera, C. grandiflora, and C. papaya present high stabilities and have potential uses in the food industry.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Interestingly, C. procera and C. grandiflora latex peptidases did not undergo autolysis and were active even after a 24 h incubation at 37 ºC (Freitas et al, 2016). All these biochemical characteristics strengthen the evidence that peptidases from C. procera, C. grandiflora, and C. papaya present high stabilities and have potential uses in the food industry.…”
Section: Discussionsupporting
confidence: 61%
“…The presence of certain ions can also be an important element in enzymatic reactions, since they can decrease the activity, or even inactivate enzymes. The calcium ions, abundant in milk, did not affect the proteolytic activity of C. procera, C. grandiflora, and C. papaya, even at 1 M CaCl2 (Freitas et al, 2016). Time can also limit enzymatic reactions catalysed by peptidases, since these enzymes can be inactivated by autodigestion (Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This index was sufficiently high to justify the use of this enzyme extract as an appropriate substitute of calf rennet. [65] According to a recent study on plant rennets, [67] Calotropis procera and Cryptostegia grandiflora latex fractions were found to be good sources of milk-clotting proteases. Both coagulant fractions were able to produce similar SDS-PAGE and RP-HPLC profiles of the κ-casein peptides, to those obtained for commercial chymosin.…”
Section: Evaluation Of Enzymatic Activities Of Plant Rennetsmentioning
confidence: 99%
“…The results revealed that M. citrifolia had the most rapid coagulation time compared to those of M. indica and rennet. The ratio of milk coagulation activity to proteolytic activity (MCA/PA) is a crucial benchmark in determining the peptidase potential to be used as coagulants in cheese industry (Arima et al, 1970;Freitas et al, 2016). In addition, the ratio is regarded as an index to assess possible rennet substitutions (Hashim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%